Increased Carbonic Anhydrase Activity is Associated with Sleep Apnea Severity and Related Hypoxemia - Wang, Tengyu (Sleep, 2015)
STUDY OBJECTIVES: The catalytic function of the enzyme carbonic anhydrase (CA) plays a fundamental role in carbon dioxide (CO(2)), proton (H(+)), and bicarbonate (HCO(3)(-)) homeostasis. Hypoxia and tissue acidosis have been proposed to increase physiological CA activity in various compartments of the body. We hypothesized that CA activity in blood is upregulated in patients with obstructive sleep apnea (OSA). DESIGN: Cross-sectional analysis of a sleep clinic cohort. SETTINGS: Sleep laboratory at a university hospital. PARTICIPANTS: Seventy referred patients with suspected OSA (48 males, age 54 ± 13 y, apnea-hypopnea index (AHI) median [interquartile range] 21 [8–41] n/h). INTERVENTIONS: N/A. MEASUREMENTS AND RESULTS: In-laboratory cardiorespiratory polygraphy was used to assess OSA. CA activity was determined by an in vitro assay that quantifies the pH change reflecting the conversion of CO(2) and H(2)O to HCO(3)(-) and H(+). CA activity was positively associated with AHI and 4% oxygen desaturation index (ODI4) (Spearman correlation r = 0.44 and 0.47, both P < 0.001). The associations (CA activity versus logAHI and CA versus logODI4) were independent of sex, age, body mass index, presleep oxygen saturation, nocturnal oxygen saturation, hypertension status, and use of diuretic medication in two generalized linear models (P = 0.007 and 0.011, respectively). Sitting diastolic blood pressure was associated with CA activity after adjustment of sex, age, body mass index, mean oxygen saturation, and AHI (P = 0.046). CONCLUSIONS: Carbonic anhydrase (CA) activity increased with apnea-hypopnea index and related nocturnal hypoxemia measures in patients with obstructive sleep apnea (OSA). Altered CA activity may constitute a component that modulates respiratory control and hemodynamic regulation in patients with OSA. CITATION: Wang T, Eskandari D, Zou D, Grote L, Hedner J. Increased carbonic anhydrase activity is associated with sleep apnea severity and related hypoxemia. SLEEP 2015;38(7):1067–1073.